Metaphor and English Promotional Tourism Discourse: Systematic-narrative Hybrid Literature Review and Future Research Areas - Nazi Iritspukhova (Anglica. An International Journal of English Studies)
As there is lack of a research synthesis on metaphor in tourism discourse up to date, the paper offers a novel contribution by summarising empirical literature on metaphor use in print and digital tourism promotional materials and identifying the existing research gaps. The review uncovers that figuration is largely underexplored in tourism promotion literature revealing only general functions and specific examples of metaphors. The paper also presents preliminary results from ongoing research on metaphor use in English e-promotional tourism discourse. Thereby, the paper provides new insights into metaphor as a multifaceted phenomenon integrating discursive, conceptual, and cultural elements and contributes to our understanding of the role of metaphor in cross-cultural communication.